Effects of maximal strength training on sprint performance of competitive swimmers - Strass, D. (Swimming Science V, 1988)
Recent laboratory research has indicated that explosive type maximal strength training regimens change isometric force-time (f-t) characteristics (rate of force development, maximal force) in different forms (Biihrle, 1985; Hakkinen & Komi, 1986; Komi, Karlsson, Tesch, Suominen, & Heikkinen, 1982; Schmidtbleicher, 1980, Schmidtbleicher & Biihrle, 1987). These results show considerable improvements in the rate of force development with minor increases in maximal force. These different improvements in f-t characteristics are induced by specific changes in voluntary neuromuscular performance capacity. In addition to pure maximal force, which is primarily influenced by hypertrophy (Moritani & De Vries, 1979), explosive maximal force production, which is affected by neural activation (Hakkinen & Komi, 1985), is an important component of the underwater arm movement in sprint swimming. The effects of strength training on sprint swimming performance have been investigated by Moffroid and Whipple (1970); Pipes and Wilmore (1976); Costill, Sharp, and Troup (1980); and Miyashita and Kanehisa (1983). Training methods and equipment were used in these studies that included weight training, and isometric, isotonic, and isokinetic exercises. However, very few studies have dealt with the question of whether the gains in muscular output after explosive type maximal strength training result in the improvement of sprint swimming performance (H6tke, 1985). The present pilot study, therefore, was designed to examine the effects of strength training with short-term explosive maximal dynamic contractions against high loads on thef-t characteristics and parameters of sprint swimming performance (speed, stroke frequency, stroke length) and their possible relationships.